Increasing Evidence for the Association of Breast Implant-Associated Anaplastic Large Cell Lymphoma and Li Fraumeni Syndrome. (16th July 2019) - Adlard, Julian; Burton, Cathy; Turton, Philip
Abstract : We report a case of breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) occurring in a 53-year-old female with Li Fraumeni syndrome (LFS) with a prior history of breast cancer. We present the clinical features, investigation, and management of this patient and potential mechanisms that could explain the increasing association of BIA-ALCL and LFS.